Formation of Practical and Activity Competence of Future Music Teachers During Pedagogical Practice - Sovik, Tetiana (Pedagogical Discourse, 2022)
The article deals with the problem of formation of practical competence of future music teachers. Based on the analysis of scientific sources and practical experience on this issue, the definition of the concept of "practical-activity competence of the future music teacher" has been clarified as the ability to apply the complex of theoretical and methodological knowledge, practical abilities and skills acquired during studies at a higher education institution in practice in institutions general secondary education. It was determined that the components of practical-activity competence are professional orientation (interest in the future profession of a music teacher), theoretical and methodical literacy (knowledge of musical education methods), practical training (the ability to apply the acquired theoretical knowledge of musical disciplines during the course of Industrial Pedagogical Practice in institutions of general secondary education). The main functions of the practical training of the future music teacher are considered: educational (mastery of professional knowledge necessary for the future profession), educational (education of a cultural, musically educated personality of the music teacher), motivational (activation of interest in the future profession), emotional (formation of a complete emotional sphere student by means of the best examples of musical art), developing (development of musical abilities of the future teacher of musical art: improvement of performance skills). The main tasks and learning outcomes during the Industrial Pedagogical Practice period in general secondary education institutions have been determined. The stages (preparatory, adaptive, formative) of the formation of practical-activity competence of higher education graduates of the specialty Secondary Education (Musical Art) during the course of Industrial Pedagogical Practice in institutions of general secondary education are highlighted.